Formation of demand for innovations by means of event marketing - Masalab, O. V. (WSEH, 2024)
The report determines that the formation of demand for innovations through event marketing is an important aspect of the modern marketing strategy. Event marketing allows brands not only to present their innovative products or services, but also to create an emotional connection with the audience, which contributes to the formation of demand.
Формування попиту на інновації за допомогою івент-маркетингу
Keywords: demand generation; innovations; new products; event marketing; promotion; efficiency